Algerian EFL Secondary School Teachers’ Professional Development: an Institutional Obligation or a Personal Pursuit - ADJADJ , Djalila; MOULEME, Manel (Journal of Human Sciences, 2025)
This paper aims at investigating Algerian EFL secondary school teachers’ professional development activities and whether they consider them as an institutional obligation or a personal pursuit. To reach this aim, a quantitative approach is adopted based on an online questionnaire, which was addressed to 40 teachers from different secondary schools in the districts of Constantine and Oum El Bouaghi via social media networks such as Facebook groups. The data obtained from the questionnaire revealed that the participants engaged in few professional development activities. They often practice self-monitoring and peer observation, and they sometimes use teaching portfolios. Moreover, workshops are the least practiced activities, yet teachers claim that they are good opportunities to discuss different issues related to their work. The findings also showed that teachers regard their professional development a personal pursuit rather than an institutional obligation. In short, professional development is considered a responsibility driven by personal motivation.